14th International Workshop on Breast Imaging (IWBI 2018) 2018
DOI: 10.1117/12.2318058
|View full text |Cite
|
Sign up to set email alerts
|

Classification of mammographic microcalcification clusters with machine learning confidence levels

Abstract: This paper presents a novel investigation of machine learning performance by examining probability outputs in conjunction with classification accuracy (CA) and area under the curve (AU C). One of the main issues in the deployment of computer-aided detection/diagnosis (CAD) systems is lack of 'trust' of clinicians in the CAD system, increasing the possibility of the system not being used. Whilst most authors evaluate the performance of their breast CAD systems based on CA and AU C, we study the distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…This is similar to other tasks such as microcalcification or lesion detection as they dont usually appear close to the pectoral muscle boundary (Rampun et al, 2018c).…”
Section: Up-sampling Resulting Contoursupporting
confidence: 71%
“…This is similar to other tasks such as microcalcification or lesion detection as they dont usually appear close to the pectoral muscle boundary (Rampun et al, 2018c).…”
Section: Up-sampling Resulting Contoursupporting
confidence: 71%
“…This study could lead to a development of a new evaluation metric which could be used to estimate the degree of certainty of the system, hence provides positive potential impacts of CAD systems [8,17]. This study indicates that using A and AU C in conjunction with confidence measure to provide a more transparent representation of the actual reliability of CAD systems which is similar to our previous study [18]. In conclusion, we have studied the reliability of the confidence measures of 11 different classifiers for the breast mass classification which indicates that although a system could produce high accuracy or AU C, it does not provide a full indication about the confidence reliability of the system.…”
supporting
confidence: 80%
“…Exploratory studies for breast mass classification [ 153 ] and classification of microcalcifications in mammograms [ 154 ] using data sets taken from the Curated Breast Imaging Subset of DDSM [ 155 ] showed that although most classifiers produce similar overall ACC and AUC values, their performances differ significantly in terms of confidence measure. High ACC or AUC does not provide a full indication of the confidence level of a CAD system.…”
Section: Resultsmentioning
confidence: 99%